The groundnut crop - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The groundnut crop: a scientific basis for improvement Edited by J Smartt 1994 752pp price UKL89.00 ISBN 0 41240 820 1